Influence of childhood trauma on diagnosis and substance use in first-episode psychosis. (September 2017) - Tomassi, S.; Tosato, S.; Mondelli, V.; Faravelli, C.; Lasalvia, A.; Fioravanti, G.; Bonetto, C.; Fioritti, A.; Cremonese, C.; Parrino, R. Lo; De Santi, K.; Meneghelli, A.; et al.
Abstract : Background: Childhood trauma has been significantly associated with first-episode psychosis, affective dysfunction and substance use. Aims: To test whether people with first-episode psychosis who had experienced childhood trauma, when compared with those who had not, showed a higher rate of affective psychosis and an increased lifetime rate of substance use. Method: The sample comprised 345 participants with first-episode psychosis (58% male, mean age 29.8 years, s.d.=9.7). Results: Severe sexual abuse was significantly associated with a diagnosis of affective psychosis (χ 2 =4.9, P =0.04) and with higher rates of lifetime use of cannabis (68% v. 41%; P = 0.02) and heroin (20% v. 5%; P =0.02). Severe physical abuse was associated with increased lifetime use of heroin (15% v. 5%; P = 0.03) and cocaine (32% v. 17%; P = 0.05). Conclusions: Patients with first-episode psychosis exposed to childhood trauma appear to constitute a distinctive subgroup in terms of diagnosis and lifetime substance use.